The impact of external factors on ICT usage practices at UNESCO World Heritage Sites - Thereza Mugobi; Shogo Mlozi (Journal of Tourism, Heritage & Services Marketing, 2021)
Purpose: This study aimed to assess the external factors influencing ICT usage at UNESCO World Heritage Sites (WHS), focusing on exploring practices Tanzania. The study proposed and tested two hypotheses: a) there is a significant relationship between perceived pressure from competitors and ICT usage in WHS, and b) there is a significant relationship between perceived pressure from customers/visitors and ICT usage in WHS. Methods: Data for this study were collected from 238 UNESCO World Heritage Site decision-makers in Tanzania. These respondents were stratified into three strata, based on UNESCO's categorization of site type (nature, mixed, and culture). Systematic random sampling was used to select respondents from each stratum according to their ratio in the total population. Testing of the hypotheses involved structural equation modeling (SEM) analysis. Chi-square/Degree of freedom (CMIN/DF), Goodness of Fit Index (GFI), Tucker-Lewis Index (TLI), comparative fit index (CFI), and root mean square error of approximation (RMSEA) were used as criteria for estimation of goodness of fit indices. Results: The findings indicated that perceived competitive pressure and perceived pressure from customers had a positive influence on ICT usage at WHS. This study confirms the T.O.E theory by Tornatzky and Fleischer (1990), which postulate that decision to use a new ICT system within the organization is determined by environmental factors which include features in which the firms conduct business such as competitors and its customers. Implications: For the success of any tourism business, particularly UNESCO World Heritage Sites, ICT usage is inevitable for their site's performance. For destination management organisations, the current study is important for policy formulation, particularly in relation to ICT usage by the tourism industry at the destination to create a conducive business environment that may assist tourism growth related to World Heritage Sites.
Keywords: N7; L83; Z39; 330; UNESCO World Heritage Sites; tourism policy; heritage tourism; ICT usage; Tanzania